A Comparison of Risks and Benefits Regarding Hip Arthroplasty Fixation. (1st November 2021) - Matthias, Julia; Bostrom, Mathias P.; Lane, Joseph M.
Abstract : Since the field-changing invention of noncemented hip arthroplasty fixation in the 1980s, noncemented fixation has been progressively replacing cemented fixation. However, analyses of fixation frequencies reveal new patterns in cement versus noncemented preferences. Although cementation is again gaining ground in the United States, noncemented models remain the dominant fixation mode, seen in more than 90% of all hip arthroplasties. This stark preference is likely driven by concerns regarding implant durability and patient safety. Although advances in surgical techniques, intensive perioperative care, and improved instrument have evolved in both methods, data from large arthroplasty registries reveal shifting risks in contemporary hip arthroplasty, calling the use of noncemented fixation into question. Varying risk profiles regarding sex, age, or health comorbidities and morphological and functional differences necessitate personalized risk assessments. Furthermore, certain patient populations, based on the literature and data from large registries, have superior outcomes from cemented hip arthroplasty techniques. Therefore, we wanted to critically evaluate the method of arthroplasty fixation in primary hip arthroplasties for unique patient populations.